2003
DOI: 10.4049/jimmunol.170.9.4475
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Regulates the CD4/CD8 T Cell Differentiation Ratio

Abstract: The signaling pathways that control T cell differentiation have only begun to be elucidated. Using T cell lines, it has been shown that class IA phosphatidylinositol 3-kinase (PI3K), a heterodimer composed of a p85 regulatory and a p110 catalytic subunit, is activated after TCR stimulation. Nonetheless, the contribution of p85/p110 PI3K isoforms in T cell development has not been described. Mice deficient in the other family of class I PI3K, p110γ, which is regulated by G protein-coupled receptors, exhibit red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 51 publications
5
66
2
Order By: Relevance
“…Expression of a dominant negative form of p85 (⌬p85) in fetal thymic organ culture inhibited IL-7R-mediated proliferation and/or survival of thymocyte precursors without altering thymocyte differentiation, as assessed by the percentages of double-negative (DN), double-positive (DP), and single-positive (SP) thymocytes (12). In contrast, effects on the CD4/CD8 differentiation ratio have been reported in neonate p110␥ Ϫ/Ϫ animals and transgenic mice expressing the mildly activating class I A p65 PI3K transgene (13). Roles for both types of class I PI3Ks in thymocyte emigration are indicated by the observations that CD4 T cell appearance in the periphery (as assessed by thymic FITC or BrdU labeling) is potentiated by expression of the p65 PI3K transgene and that CD4 and CD8 thymocyte exits are inhibited by p110␥ deficiency (13).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Expression of a dominant negative form of p85 (⌬p85) in fetal thymic organ culture inhibited IL-7R-mediated proliferation and/or survival of thymocyte precursors without altering thymocyte differentiation, as assessed by the percentages of double-negative (DN), double-positive (DP), and single-positive (SP) thymocytes (12). In contrast, effects on the CD4/CD8 differentiation ratio have been reported in neonate p110␥ Ϫ/Ϫ animals and transgenic mice expressing the mildly activating class I A p65 PI3K transgene (13). Roles for both types of class I PI3Ks in thymocyte emigration are indicated by the observations that CD4 T cell appearance in the periphery (as assessed by thymic FITC or BrdU labeling) is potentiated by expression of the p65 PI3K transgene and that CD4 and CD8 thymocyte exits are inhibited by p110␥ deficiency (13).…”
mentioning
confidence: 87%
“…In contrast, effects on the CD4/CD8 differentiation ratio have been reported in neonate p110␥ Ϫ/Ϫ animals and transgenic mice expressing the mildly activating class I A p65 PI3K transgene (13). Roles for both types of class I PI3Ks in thymocyte emigration are indicated by the observations that CD4 T cell appearance in the periphery (as assessed by thymic FITC or BrdU labeling) is potentiated by expression of the p65 PI3K transgene and that CD4 and CD8 thymocyte exits are inhibited by p110␥ deficiency (13). We thus sought to further delineate the role of class I A PI3K in thymocyte egress.…”
mentioning
confidence: 90%
“…Most of the previous work on PI3Ks in lymphocyte activation have focused on the class I PI3Ks (p110 α, β, γ, and δ), which are responsible for the acute rise in PI(3,4,5)P 3 following antigen-receptor activation (5,6). Studies in knockout mice have demonstrated that p110δ and p110γ play partly redundant functions in T-cell activation, and are most important for T-cell receptor (TCR) signaling by peripheral T cells, as well as for T-cell development and survival (7)(8)(9)(10)(11). Although the exact role for PI(3,4,5)P 3 in T-cell activation is still controversial, recruitment and activation of a number of plekstrin-homology containing proteins by PI(3,4,5)P 3 is critical.…”
mentioning
confidence: 99%
“…Interestingly, it was shown that introduction of a constitutively active mutant of class IA PI3K was able to restore the defect of p110␥ Ϫ/Ϫ mice (28). Rodríguez-Borlado et al (28) have reported that forced expression of a mutant form of p85␣ leading to activation of catalytic subunits resulted in acceleration of CD4 SP cell differentiation without affecting CD8 SP cells. In contrast, tg mice established by Barbee and Alberola-Ila (12) that express a portion of p110␣ subunit that lacks catalytic activity but binds p85␣, leading to activation of the endogenous catalytic subunit showed no difference in CD4/CD8 commitment.…”
Section: Discussionmentioning
confidence: 99%